SINTESIS DAN KARAKTERISASI KIMIA DARI METIL EUGENIL FORMAT - Hanoch J Sohilait (Molluca Journal of Chemistry Education (MJoCE), 2012)
Methyleugenyl formate has been synthezed, purified and chemically characterized using nuclear magnetic resonance spectroscopy, fourier transform infra red and gas chromatography-mass spectrometry. The reaction of methyleugenol with formic acid yield 62,69% methyleugenyl formate